2011
DOI: 10.1007/s10787-011-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Withania somnifera on pristane-induced model of SLE

Abstract: Systemic lupus erythematosus commonly known as lupus is an intricate disorder with multiple organ involvement characterized primarily by inflammation caused due to deposition of immune-complexes formed by production of autoantibodies against nuclear, nucleolar as well as cytoplasmic self-antigens. Lack of availability of suitable treatments or treatments that are only symptomatic calls for investigation of possible modalities. Withania somnifera with its immunomodulatory properties is prescribed for arthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
13
0
2
Order By: Relevance
“…for review) contributing to mitochondrial function and inducing cell death. In this regard, it has widely reported that Wse show a potent inhibitory effect on inflammatory markers such as ROS in a mouse model of lupus4647. Interestingly Wse reduced rotenone-induced oxidative impairment and mitochondrial respiratory chain enzymes and such impairments were responsible for reduced locomotor deficits and lethality in a Drosophila melanogaster model of Parkinson induced by rotenone, a naturally occurring common pesticide which specifically inhibits mitochondrial complex-I activity48.…”
Section: Discussionmentioning
confidence: 98%
“…for review) contributing to mitochondrial function and inducing cell death. In this regard, it has widely reported that Wse show a potent inhibitory effect on inflammatory markers such as ROS in a mouse model of lupus4647. Interestingly Wse reduced rotenone-induced oxidative impairment and mitochondrial respiratory chain enzymes and such impairments were responsible for reduced locomotor deficits and lethality in a Drosophila melanogaster model of Parkinson induced by rotenone, a naturally occurring common pesticide which specifically inhibits mitochondrial complex-I activity48.…”
Section: Discussionmentioning
confidence: 98%
“…Given the role of inflammation in injury and progression to dysfunction via pro-fibrogenic mechanisms, strategies to attenuate inflammation are promising therapeutics. There are a number of studies suggesting that botanicals are anti-inflammatory [ 29 31 , 36 ]; however, the molecular pathways targeted by many of these remains poorly defined. In our studies, we developed an in vitro model to screen botanical extracts for anti-inflammatory cells in a rat proximal tubular epithelial cell line, NRK-52E, since the proximal tubular epithelium is both a source [ 5 ] and target of inflammation in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear as to whether these effects extend to renoprotection and, in fact, an elderberry-rich extract enriched in anthocyanins did not improve renal function in a small clinical trial of postmenopausal women [ 32 ]. In contrast, ashwagandha ( Withania somnifera ) has been demonstrated to be renoprotective via both antioxidant [ 33 – 35 ] and anti-inflammatory effects [ 36 ]. The current studies were designed to screen water-soluble extracts of ashwaganda, sutherlandia and elderberry for anti-inflammatory effects in renal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, I read with great interest the recent article by Minhas et al (2012). Withania may exert a number of anti-proliferative effects besides its protective role in SLE.…”
mentioning
confidence: 99%